Differences in mortality between temporary and permanent workers: results from the Rome Longitudinal Study - Marina Davoli; Nera Agabiti; Giulia Cesaroni; Angelo Nardi; Luca Dei Bardi (BMJ Open, 2022)
Objective Precarious employment is characterised by instability, lack of protection and economic vulnerability. The objective of this study was to assess the association between temporary contracts and mortality.Design Cohort study.Setting Rome, Italy.Participants All employees, aged 25–65 years, from the Rome Longitudinal Study, followed from 21 October 2001 to the first date among death, migration from Rome, or 31 December 2015.Primary and secondary outcome measures We investigated all-cause, cardiovascular and accidental mortality. We considered gender, age, place of birth, education, temporary versus permanent contract and sector of employment. We used Cox models to investigate the association between type of contract and total, cardiovascular and accidental mortality in men and women, overall and by employment sector.Results We analysed 597 834 subjects. The proportion of temporary contracts varied by gender (9.6% in men and 13.3% in women) and by employment sector, ranging from 4.5% (public administration) to 27% (recreational, cultural, sports activities) in men. During the study period, 21 136 subjects died. Men with temporary contracts, compared with those with permanent positions, had greater overall mortality risk (HR=1.16, 95% CI 1.09 to 1.24), cardiovascular mortality (HR=1.29, 95% CI 1.14 to 1.45) and accidental mortality (HR=1.27, 95% CI 1.04 to 1.57). In men, the association varied widely among different economic sectors, with greater risks in the industry, building constructions and social services sectors. In women, there was no evidence of association between temporary contracts and mortality. A statistically significant association between temporary contracts and mortality in women was found in the sector of sales and transports only.Conclusions Temporary work should be considered a determinant of health, particularly for specific economic sectors.